The National Income of the Soviet Union - Litoshenko, L. N. (Quarterly Journal of Economics, 1927)
I. Purpose and methods of the inquiry, 70. — II. Net Production in the Soviet Union, 74. — III. Net Production by industries: Comparison with the United States, 76. — IV. Russian income per head compared with that in other countries, 79. — V. Proportion of state and private industries in Russia, 83. — VI. Distribution of income between occupations in Russia and in the United States, 85. — VII. Distribution of income between individuals in Russia and in the United States, 88.